2017
DOI: 10.1103/physreve.95.013105
|View full text |Cite
|
Sign up to set email alerts
|

Band instability in near-critical fluids subjected to vibration under weightlessness

Abstract: Periodical patterns (bands) developing at the interface of two immiscible fluids under vibration parallel to interface are observed under zero-gravity conditions. Fluids are slightly below their liquid-vapor critical point where they behave in a scaled, universal manner. In addition, liquid and vapor densities are close and surface tension is very low. Linear stability analyses and direct numerical simulation show that this instability, although comparable to the frozen wave instability observed in a gravity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 21 publications
3
38
1
Order By: Relevance
“…At low‐intensity vibration, the Kelvin‐Helmholtz instability serves as the dominant factor for promoting mixing. At the same time, it is known that there is no instability threshold for the Kelvin‐Helmholtz instability in zero‐gravity conditions . However, when the vibration intensity is very weak, only a very small deformation of the interface can be observed and the mixing is still dominated by diffusion.…”
Section: Resultsmentioning
confidence: 62%
“…At low‐intensity vibration, the Kelvin‐Helmholtz instability serves as the dominant factor for promoting mixing. At the same time, it is known that there is no instability threshold for the Kelvin‐Helmholtz instability in zero‐gravity conditions . However, when the vibration intensity is very weak, only a very small deformation of the interface can be observed and the mixing is still dominated by diffusion.…”
Section: Resultsmentioning
confidence: 62%
“…In this section, we analyse the instabilities when the direction of vibration is parallel to the direction of temperature gradient. It is well established that a two-phase fluid (miscible or immiscible)can exhibit parametric instabilities when subjected to vibrations perpendicular to its interface [18,33,34]. In the present study, when the SCF close to its critical point is quenched and simultaneously subjected to vibrations along the direction of temperature gradient, the TBL becomes unstable leading to the appearance of waves or finger-like structures.…”
Section: B Parametric Instabilitiesmentioning
confidence: 58%
“…Experimental and numerical studies with supercritical CO 2 and SF 6 under weightlessness have reported evidences of such instabilities as described in [12][13][14][15]. Experiments with supercritical have also been reported in literature where micro-gravity conditions were artificially simulated by means of a strong magnetic field [16][17][18][19][20][21]. When supercritical close to the critical point is simultaneously quenched and subjected to mechanical vibrations, finger-like structures were observed normal to the direction of vibration.…”
mentioning
confidence: 99%
“…The first experimental studies on the usage of vibrations for stabilizing otherwise unstable configurations of multiphase fluid systems were reported by Wolf (1961Wolf ( , 1970. Under the weightlessness conditions, the demand for such a control tool even increases because of the necessity to maintain stratification of fluids or control convection for diverse technological systems, which is well highlighted by the ongoing research on the subject (Thiele et al 2006, Mialdun et al 2008, Shklyaev et al 2009, Nepomnyashchy and Simanovskii 2013, Gaponenko and Shevtsova 2016, Bratsun et al 2015, Lappa 2016, Smorodin et al 2017, Lyubimova et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The equations were derived below the instability threshold within the framework of the long-wavelength approximation for the case of equal thickness of layers. Simultaneously, the understanding of strongly nonlinear regimes of the dynamics of the interface in low-viscosity liquids above the instability threshold was significantly advanced in (Lyubimova et al 2017) by means of numerical simulation accompanied by analytical estimates.…”
Section: Introductionmentioning
confidence: 99%